Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1071/rdv27n1ab67
|View full text |Cite
|
Sign up to set email alerts
|

67 Effects of Antioxidants Lactoferrin and Catalase on Stallion Frozen Semen

Abstract: During cryopreservation, the sperm were submitted to an increased generation of reactive oxygen species. Furthermore, because of the large portion of seminal plasma removal, there is a decrease of sperm antioxidant protection. Addition of antioxidants proteins found in seminal plasma, such as lactoferrin (Lf) and catalase (Cat), to the freezing semen extenders could protect the sperm during cryopreservation. Lactoferrin is a transferrin, which prevents the hydroxyl radicals generation, and Cat plays an antioxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Recent studies have identified molecules that improve some semen parameters. This has been attributed mainly to their antioxidant nature (Lisboaet al 2012;Gibb et al 2013, Martins et al 2015.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have identified molecules that improve some semen parameters. This has been attributed mainly to their antioxidant nature (Lisboaet al 2012;Gibb et al 2013, Martins et al 2015.…”
Section: Resultsmentioning
confidence: 99%
“…The increase in the generation of reactive oxygen species (ROS), the decrease in antioxidant defense and the oxidation of lipids and proteins in stallion semen once it is cryopreserved (Morteet al 2008, Macias-Garcia et al 2011, have motivated a great deal of research on molecules or substances that strengthen its protection against oxidative stress (Barros et al 2012, Gibb et al 2013Martins et al 2015). In spite of this, in most cases results have been far from encouraging (Hussain et al 2011;Martins et al 2012).…”
mentioning
confidence: 99%